Halal Certification of Cryptocurrency: A Framework for Strengthening Trust in Shariah-Compliant Digital Finance - Muchammad Aqib Junaidi; Reka Dewantara; Nur Chanifah (Indonesian Academy of Social and Religious Research (IASRR), 2025)
Cryptocurrency has emerged as a significant global innovation that continues to stimulate debates regarding its permissibility within the framework of Islamic finance. This study examines Islamic legal perspectives on cryptocurrency by analyzing contemporary fatwas, academic discussions, and authoritative literature in the fields of ushul fiqh and Islamic economics. Using a qualitative descriptive method, the research identifies key legal considerations such as the presence of gharar, maysir, and riba, which determine the Shariah status of digital assets. The findings reveal that, in principle, cryptocurrency may be considered halal as a digital asset when it has straightforward utility, is transparent, and used for lawful economic activities. Several scholars view cryptocurrency as permissible when supported by reliable technology, adequate regulatory structures, and mechanisms that prevent fraud and speculation. Conversely, other scholars classify it as haram due to its extreme price volatility, speculative trading practices, lack of tangible underlying value, and inadequate regulatory oversight in many jurisdictions. To bridge these differing views, the study proposes developing Shariah-based assessment frameworks and halal certification mechanisms to provide greater legal clarity for Muslim investors. Furthermore, it underscores the urgent need for stronger regulatory policies and the advancement of Shariah-compliant blockchain systems that ensure ethical, transparent, and stable digital financial transactions.